Penggunaan Aplikasi Quizizz Paper Mode dalam Peningkatan Motivasi Belajar Mata Pelajaran Pendidikan Agama Islam Kelas VII SMP Islam Tarbiyyatul Falah Karawang - Balqista Yolanda Azizah; Iwan Hermawan; Nur Aini Farida (STAI Terpadu Yogyakarta, 2023)
The purpose of this research is to describe how it is used, supporting and inhibiting factors, and the impact of Using The Quizizz Paper Mode Application In Increasing Motivation To Learn Islamic Religious Education For Class VII At Islamic Middle School Tarbiyyatul Falah Karawang. This study used a qualitative approach with a descriptive research type located at Tarbiyyatul Falah Islamic Middle School Karawang. The results of this study indicate that: 1) The use of the Quizizz Paper Mode Application in Increasing Learning Motivation in Islamic Religious Education Subjects for Class VII at Islamic Middle School Tarbiyyatul Falah Karawang is used as a learning medium, precisely as a medium for evaluating learning and strengthening material after learning is complete. 2) Supporting factors for the use of Quizizz Paper Mode include: the availability of devices (handphones, laptops, and LCD projectors), does not require large quota consumption, the affordability of cellular networks and wifi networks, and the availability of printed and laminated barcode paper that can be used at all classes. While the inhibiting factor is an unstable network for teachers. 3) The impact of using the Quizizz Paper Mode application is that students become enthusiastic and motivated in the continuity of the learning process, can attract students' attention in delivering material so they don't get bored, make students enthusiastic in learning, and make it easier for students to understand learning.